Accommodation: a cognitive heuristic for background information - Misha-Laura Müller (Anglophonia)
Presuppositions are usually defined as a linguistic means to convey background information, which require very little cognitive effort to be interpreted (Sperber & Wilson [1986] 1995: 706). As for the accommodation of presupposition, it is defined as a process by which the listener updates – also at minimal costs – the presupposed information whenever it is not mutually shared. Accommodation is generally considered to be a voluntary process (cf. von Fintel 2000), which may be inhibited when information is problematic or contradicts the listener’s prior beliefs.The aim of this paper is to challenge the idea that accommodation operates only on traditional presuppositional triggers (Beaver 2001). Furthermore, I argue against the claim that this process is autonomous and always under voluntary control. To do so, I first show how traditional triggers form a heterogeneous class that is difficult to capture in terms of attention requirements and cognitive costs (see Domaneschi et al. 2014). I then present discursive presuppositions (de Saussure 2013) and underline their similarities with semantic presuppositions. I show to what extent accommodation is likely to be a process dedicated to both semantic and discursive presuppositions. Finally, I argue that accommodation can be viewed as a cognitive heuristic for background information, involving minimal attention. Such an approach should allow to explain why presupposition accommodation is likely to bypass the listener’s epistemic vigilance (Sperber et al. 2010), as evidenced by experiments in experimental psychology (Bredart & Modolo 1988; Reder & Kusbit 1991; Park & Reder 2004 inter alia).